Influence of Strength, Sprint Running, and Combined Strength and Sprint Running Training on Short Sprint Performance in Young Adults - Marques, M. C.; Gabbett, T. J.; Marinho, D. A.; Blazevich, A. J.; Sousa, A.; van den Tillaar, R.; Izquierdo, M. (International Journal of Sports Medicine, 2015)
The purpose of this study was to assess the degree of transference of 6 weeks of full squat vs. full squat plus sprint running training to short (ranged from 0–10 to 0–30 m) sprint running performance in non-athletes. We hypothesized that a speed-full-squat training regimen could enhance squat strength and power with simultaneous improvements in short sprint performance. 122 physically active adults (age: 20.5±2.5 years; body mass: 65.8±6.1 kg; height: 1.71±0.08 m) were randomly divided into 4 groups: full squat training (n=36), combined full squat and sprint training (n=32), speed training only (n=34) and non-training control group (n=20). Each training group completed 2 sessions per week over 6 weeks, while the control group performed only their normal physical activity. Sprint performance was improved after sprint running or full squat training alone (1.7% and 1.8% P<0.05, respectively), however larger enhancements (2.3%; P<0.01) were observed after the combined full squat plus sprint training intervention. These results suggest that in recreationally active adults, combined full squat and sprint training provides a greater stimulus for improving sprint performance than either modality alone.
Keywords: velocity; sprint; full-squat; transfer; combined training